The abandoned empress. 3 - 인아 (Yen Press, 2022)
""WHAT IF I'M ABANDONED YET AGAIN?" Thanks to the boisterous Carsein and her new imperial bodyguards, Aristia is able to put her desperation aside and find her smile again. But when the dreaded invitation to the crown prince's coming-of-age ceremony arrives before her father can return from the border regions, she's overwhelmed with the daunting prospect of announcing her plans for the future to the emperor all by herself. If only there were just one person, one friend she could trust, to whom she could tell her story..."-- page [4] of cover.